TOED Preservation (TOED Education) at Adiwiyata School As an Effort to Implement Healthy Lifestyle - Yasa, Arnelia Dwi; Sulistyowati, Prihatin (JURNAL WIDYA LAKSANA, 2018)
AbstractSDN Tanjungrejo 2 is an Adiwiyata school located in Kecamatan Sukun Malang. SDN Tanjungrejo 2 page is filled with shade trees and ornamental plants whereas TOGA is not found there. Students do not know the type, benefits. This devotion aims to improve students understanding of the types, benefits, ways of planting and processing of toga into herbal medicine through TOGA preservation program in Adiwiyata School.TOGA preservation as an effort to back to nature movement, increasing space green field at SDN Tanjungrejo 2 Malang, live pharmacy learning media and herbal medicine. The TOGA preservation activities at SDN Tanjungrejo 2 begin with the introduction of TOGA type and benefit, TOGA processing into herbal medicine, TOGA planting on the vertical shelf. Activity is said to be successful because of the N-Gain score score, students understanding of TOGA in medium and high category.Â Keywords: TOED, adiwiyata school, healthy lifestyle